Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1677/jme.0.0200305
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing events in the coding region of the cytochrome P450 aromatase gene in male rat germ cells

Abstract: Expression of cytochrome P450 mRNA in rat germ cells was characterized by reverse transcription PCR with various primers located at the 3 -end of the coding region. At least two unusual isoforms (Ex10-S and INT) of P450 aromatase (P450arom) mRNA were expressed. Analysis of their sequences demonstrated that an alternative splicing event occurred first at the exon-intron boundary of the GT consensus sequence of the last coding exon, and second in the internal 5 donor inside exon 9 used as a minor cryptic splicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 32 publications
4
17
0
2
Order By: Relevance
“…7A). Nucleotide sequence analysis of these products revealed that the shorter segment is the same as that reported by Levallet (Levallet et al 1998b) and results from an alternative splicing site on a GT dinucleotide at position 1813-1814 (Fig. 1C).…”
Section: Effects Of T 3 On P450 Arom Mrna Expression: Evidence Of Norsupporting
confidence: 82%
See 1 more Smart Citation
“…7A). Nucleotide sequence analysis of these products revealed that the shorter segment is the same as that reported by Levallet (Levallet et al 1998b) and results from an alternative splicing site on a GT dinucleotide at position 1813-1814 (Fig. 1C).…”
Section: Effects Of T 3 On P450 Arom Mrna Expression: Evidence Of Norsupporting
confidence: 82%
“…1A: upstream Aro-Ex8, 5 -GCTTCTCATCGCAGAGTAT CCGG-3 , located in exon 8; downstream Aro-Ex9, 5 -CAAGGGTAAATTCATTGGGCTTGG-3 , located in exon 9; amplified product 289 bp (Ex9)) (Levallet et al 1998a). However, for the selective detection of altered transcripts with different 3 -end regions (coding for putative inactive protein previously reported for germ cells and rat ovary (Lephart et al 1990, Levallet et al 1998b)), we used the following antisense primers: (1) Aro-Ex10, 5 -GGA ATCGTTTCAAAAGTGTAACCAG-3 , encompassing 23 nucleotides of exon 10 (1949-1973) (Fig. 1A); (2) Aro-Ex9Tr, 5 -GGCTGAAAATACCTGTAGGGA ACTCG-3 , which matches the three nucleotides before the 49 nucleotides lacking region of exon 9 and the first 23 nucleotides at the beginning of exon 10 (Fig.…”
Section: Rt-pcr Assaymentioning
confidence: 99%
“…Together with oLH, it is clear that testosterone further controls the aromatase both at the transcriptional level and in terms of biological activity. However, with a larger concentration of gonadotropin (50 ng) the Leydig cell estradiol output decreases whereas the amount of transcripts is higher suggesting, therefore, additional regulatory steps and maybe the expression of truncated P450arom mRNAs as shown previously in rat Sertoli and germ cells (Levallet et al 1998b). Consequently, our data related to the positive effects of steroid hormones on the expression of the aromatase gene indicate that besides CRE, androgen responsive elements as well as estrogen responsive elements are necessary for a full expression of the aromatase in Leydig cells.…”
Section: Discussionsupporting
confidence: 52%
“…In fact, this study has identified a new 3 0 truncated aromatase mRNA splice variant (DQ004742) expressed in bovine granulosa cells. However, this transcript variant, with orthologues in the sheep, pig and human EST libraries, consists only of exons 1-5 of the aromatase gene, and thus may have no further function following translation (Levallet et al 1998). A new gene with so far unknown functions, OSAP, identified in mouse preovulatory follicles, may be a marker of differentiated follicle development, specifically of increased E synthesis, with gene expression responding to gonadotrophic stimulation (Hennebold et al 2000, Tanaka et al 2003.…”
Section: Discussionmentioning
confidence: 99%